2002
DOI: 10.1073/pnas.192282699
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine rearranges the active site of human topoisomerase I

Abstract: 7,8-Dihydro-8-oxoguanine (8-oxoG) is the most common form of oxidative DNA damage in human cells. Biochemical studies have shown that 8-oxoG decreases the DNA cleavage activity of human topoisomerase I, an enzyme vital to DNA metabolism and stability. We present the 3.1-Å crystal structure of human topoisomerase I in noncovalent complex with a DNA oligonucleotide containing 8-oxoG at the ؉1 position in the scissile strand. We find that 8-oxoG reorganizes the active site of human topoisomerase I into an inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…Measurement of single-turnover cleavage by the human enzyme showed that oxoG modification had less than a 2-fold effect on the forward transesterification rate; the religation rate to a 5Ј-OH oxoG acceptor stand was described as comparable with an unmodified control strand (40). A recent crystal structure of human topoisomerase I bound to a DNA containing an oxoG:C base pair 3Ј of the scissile phosphate highlighted an inactive conformation of the enzyme in which the tyrosine nucleophile (mutated to Phe) was oriented away from the scissile phosphate (51). This is reminiscent of the out-of-position state of the tyrosine in the structure of the free vaccinia topoisomerase (16).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of single-turnover cleavage by the human enzyme showed that oxoG modification had less than a 2-fold effect on the forward transesterification rate; the religation rate to a 5Ј-OH oxoG acceptor stand was described as comparable with an unmodified control strand (40). A recent crystal structure of human topoisomerase I bound to a DNA containing an oxoG:C base pair 3Ј of the scissile phosphate highlighted an inactive conformation of the enzyme in which the tyrosine nucleophile (mutated to Phe) was oriented away from the scissile phosphate (51). This is reminiscent of the out-of-position state of the tyrosine in the structure of the free vaccinia topoisomerase (16).…”
Section: Discussionmentioning
confidence: 99%
“…3B -curved arrow). Crystal structures of Top1 [20][21][22] show the enzyme encircling the DNA tightly like a clamp (Fig. 3D), which accounts for the fact that Top1 controls the processive relaxation of supercoiled DNA [20,[23][24][25] Two key pharmacological properties of camptothecins need to be stressed.…”
Section: A Introduction: Mammalian Topoisomerase Families Top1 Funcmentioning
confidence: 99%
“…nicks, mismatches, abasic sites, and AraC-substituted DNA), are now known to trap TOP1-DNA cleavage complexes (20 -23). It has been recently demonstrated that oxidative base lesions such as 8-oxoG can increase TOP1 binding to DNA and also induce a 3-7-fold increase in TOP1 cleavage complexes (24,25).…”
mentioning
confidence: 99%